Coconut agrotourism model based on local wisdom for empowerment of Lombok coastal communities - mutia devi ariyana; Aulia Islamiati Yusuf; Mirriyadhil Jannah (Journal of Biology, Environment, and Edu-Tourism, 2025)
Coconut is a strategic commodity for the coastal communities of Lombok Island, but its utilization is still focused on selling raw materials, so the added value and its role in strengthening the local economy and socio-ecological resilience are not yet optimal. This research aims to formulate a sustainable coconut agrotourism development model based on local wisdom as a strategy for empowering coastal communities on Lombok Island. This study employs a descriptive qualitative approach based on secondary data, utilizing content analysis and comparative literature review methods for scientific publications, sectoral data, and policy documents from the period 2015–2025. Literature samples were selected purposively and developed using the snowball technique until information saturation was reached. These samples were then synthesized and validated using a sustainability framework and the principles of Community-Based Tourism (CBT). The study results indicate that the potential for coconut agrotourism in Lombok is very high because it is supported by a coastal agrarian ecosystem, local wisdom in coconut processing (e.g., VCO, coconut sugar, and traditional products), and an active farming community. However, this potential is hampered by weaknesses in infrastructure, human resource capacity, institutions, and digital promotion. The proposed conceptual model emphasizes strengthening community capacity, strengthening local institutions (pokdarwis, cooperatives/BUMDes), diversifying coconut-based educational tourism products and packages, and quadruple helix collaboration to achieve inclusive, competitive, and sustainable coconut agrotourism.